The role of flumazenil in generalised anxiety disorder: a pilot naturalistic open-label study with a focus on treatment resistance - Alexander T Gallo; Stephen Addis; Vlad Martyn; Hishani Ramanathan; Grace K Wilkerson; Kellie S Bennett; Sean D Hood; Hans Stampfer; Gary K Hulse (SAGE Publishing, 2023)
Background: Anxiety disorders are highly prevalent and chronic disorders with treatment resistance to current pharmacotherapies occurring in approximately one in three patients. It has been postulated that flumazenil (FMZ) is efficacious in the management of anxiety disorders via the removal of α 4 β2δ gamma-aminobutyric acid A receptors. Objective: To assess the safety and feasibility of continuous low-dose FMZ infusions for the management of generalised anxiety disorder (GAD) and collect preliminary efficacy data. Design: Uncontrolled, open-label pilot study. Method: Participants had a primary diagnosis of generalised anxiety disorder (GAD) and received two consecutive subcutaneous continuous low-dose FMZ infusions. Each infusion contained 16 mg of FMZ and was delivered over 96 ± 19.2 h. The total dose of FMZ delivered was 32 mg over approximately 8 days. Sodium valproate was given to participants at risk of seizure. The primary outcome was the change in stress and anxiety subscale scores on the Depression Anxiety Stress Scale-21 between baseline, day 8, and day 28. Results: Nine participants with a primary diagnosis of GAD were treated with subcutaneous continuous low-dose FMZ infusions; seven participants met the criteria for treatment resistance. There was a significant decrease in anxiety and stress between baseline and day 8 and baseline and day 28. There was also a significant improvement in subjective sleep quality from baseline to day 28 measured by the Jenkins Sleep Scale. No serious adverse events occurred. Conclusion: This study presents preliminary results for subcutaneous continuous low-dose FMZ's effectiveness and safety in GAD. The findings suggest that it is a safe, well-tolerated, and feasible treatment option in this group of patients. Future randomised control trials are needed in this field to determine the efficacy of this treatment.